ECONOMIC CONSEQUENCES OF INTERNAL DISPLACEMENT IN MAKURDI LOCAL GOVERNMENT AREA, BENUE STATE, NIGERIA - Angyo, Emmanuel Washima; Anyo, Stephen Terver (African Journal of Social and Behavioural Sciences, 2025)
Internal displacement has become one of the greatest human quagmires in the world today and has become a source of concern for human existence. This study examined the economic consequences of internal displacement on internally displaced persons (IDPs) in Makurdi Local Government Area of Benue State. The specific objectives were to examine the economic consequences of internal displacement among internally displaced persons in the Makurdi Local Government Area of Benue State and recommend ways of mitigating such economic consequences among internally displaced persons in Makurdi. Frustration Aggression theory was reviewed to explain the economic consequences among internally displaced persons in Makurdi LGA. The study adopted a descriptive research design. The population of the study was 164,796 IDPs living in fifteen (15) designated official and unofficial IDP camps situated in the Makurdi Local Government Area of Benue State. The sample size of the study was 400 respondents, and this was determined using Taro-Yamane’s sample size determination formula. The study employed a multistage sampling technique. The interview method and Key Informant Interview were the instruments used for data collection. Statistical Package for Social Sciences (SPSS v.21) was used to run the data, and descriptive statistics such as percentages were used to analyse univariate data. Qualitative data was analysed in themes. The findings revealed that the economic consequences of internal displacement were: loss of farmlands (77.3%), loss of assets (96.5%), job discrimination (88.0%), drop in income (73.0%), and burnt farm produce (69.5%). The study concluded that internal displacement has had dire economic consequences on IDPs in Makurdi Local Government Area of Benue State. The study recommends that the State should make policies that mandate nongovernmental and donor agencies to provide essential interventions to IDPs to ameliorate their economic challenges in their respective camps and beyond.